Media Franchising : Creative License and Collaboration in the Culture Industries - Johnson, Derek, 1979- (Book collections on Project MUSE., 2013)
While immediately recognizable throughout the U.S. and many other countries, media mainstays like X-Men, Star Trek, and Transformers achieved such familiarity through constant reincarnation. In each case, the initial success of a single product led to a long-term embrace of media franchising - a dynamic process in which media workers from different industrial positions shared in and reproduced familiar culture across television, film, comics, games, and merchandising. In this book, the author examines the corporate culture behind these production practices, as well as the collaborative and creative efforts involved in conceiving, sustaining, and sharing intellectual properties in media work worlds.